Pengaruh Pola Asuh Otoriter Orang Tua terhadap Interaksi Anak Usia Dini - Nur Shela Mardiana (Pedagogi: Jurnal Ilmu Pendidikan, 2020)
This problem is motivated by children who are always forbidden to play with their peers outside the home on the grounds that parents are afraid of children addicted to play and become lazy to learn, this is very contrary to early childhood education, because the child's world should be a world of play. Parents will definitely provide the best parenting for their children, and parents have their own parenting, including authoritarian parenting. This authoritarian parenting style of parents will usually rule with all the lives of children and do not give children to choose what they want to do, including in children's social interactions, parents will forbid children to play for all reasons. That way the child will have a personality that can the child unable to interact with the surrounding environment.